P123 The Use of Indwelling Pleural Catheters For the Management of Non-Malignant Recurrent Pleural Effusions. (19th November 2012) - Bhatnagar, R; Reid, ED; Corcoran, JP; Clive, AO; Zahan, N; Rahman, NM; Chatterji, S; Sivasothy, PR; Maskell, NA
Abstract : Although indwelling pleural catheters (IPC) are commonly used to allow the outpatient management of malignant pleural effusions, an increasing number if IPCs are being inserted to control effusions caused by non-malignant processes. This is the first UK-based series to analyse the use of IPCs in this setting. Methods: We analysed data from 3 UK hospitals with large pleural services. IPCs inserted between 2007 and June 2012 were identified retrospectively. Information was obtained from hospital records and from patients' primary physicians. Bilateral or non-sequential IPCs in a single patient were treated as separate data points. Results: 30 IPCs were inserted, with a year-on-year rise in the number of drains seen over the analysis period. The mean age of patients was 64 (range 37–92 years). 57% were male. IPCs stayed in place for a median of 95 days (IQR 41–211) before death or removal. 6 patients died with their IPC in situ. The majority of drains (47%, n=14) were inserted for the management of hepatic hydrothorax of varying aetiology (see table 1 ). 10 of these patients were given human albumin solution (HAS) intermittently with drainage. 87% of patients began with a drainage frequency of 3 times per week or greater. At final analysis only 37% of patients remained in this group, with 50% overall experiencing a reduction in drainage needs. Drainages were most often performed by community nurses (30%) or family members (30%). Complications included drain site leak (n=1), equipment failure (n=1), pleural infection (n=2) and skin infection (n=1). IPCs were removed in 54% (n=16), with 6 patients achieving successful pleurodesis. Other reasons for removal included fluid loculation (n=2), or transplant operation(n=3). 83% of patients needed no additional pleural intervention following IPC insertion. In only 1 case did the primary physician feel the insertion of the IPC was not of value. Conclusions: These data suggest the use of IPCs in the non-malignant setting is increasing. Complications were rare and most patients could be managed for extended periods in the community alone. This series would suggest that IPCs are a viable option for the management of recurrent pleural effusions of non-malignant aetiology. Dr Maskell has received an unrestricted research grant from Care Fusion, not related to this study. Dr Rahman acts as a consultant to Rocket Medical UK, not related to this study.